On the Home Front - Darian-Smith, Kate (Melbourne University Publishing, 2009)
During WWII, the people of Melbourne experienced years of social dislocation and increased government interference in all aspects of daily life. As women left the home to replace men in factories and offices, the traditional roles of women were challenged, and the presence of US soldiers raised questions about Australian identity.